Aplikasi Pembelajaran Interaktif Perkembangbiakkan Makhluk Hidup: Interactive Learning Application of Reproduction of Living Things - Christania Febrina Paat; Brave Angkasa Sugiarso; Fransisca Joanet Pontoh (Universitas Sam Ratulangi, 2022)
Abstract — Science lessons are one of the lessons that have a very important role in elementary school because they relate to what is around and what is often experienced, this lesson is important so that students can understand the natural environment well and can see everything objectively and scientifically. In an effort to provide education, of course there are learning techniques used so that the material can be conveyed well to students. At this time, in elementary schools still use conventional methods where the teacher's role is to control most of the learning or referred to as the lecture method. Here students do not take much part in learning because only the teacher has a lot of roles in the lecture method so that the process of teaching and learning activities becomes less effective, less interesting and less fun. In delivering the material conventionally the teacher uses a book as a reference material, but the book used in delivering the material only contains black and white text and images, which makes it less interesting and less clear to see. By making this interactive learning application, it is hoped that the teaching and learning process will be more effective, interesting and fun. The purpose of this research is to facilitate grade 6 elementary school students in learning the Breeding of Living Things. Interactive learning applications made based on android using the Multimedia Development Life Cycle method which starts from the stages of conceptualizing, designing, collecting materials, making, testing and distributing. Key words — Breeding, Interactive, Learning, Living Tings, Multimedia Development Life Cycle. Abstrak — Pelajaran Ilmu Pengetahuan Alam (IPA) adalah salah satu pembelajaran yang mempunyai peranan sangat penting di sekolah dasar karena berhubungan dengan apa yang ada disekitar dan apa yang sering dialami, pelajaran ini penting agar siswa dapat memahami lingkungan alam dengan baik dan bisa melihat segala sesuatu secara objektif dan ilmiah. Pada saat ini, di sekolah dasar masih menggunakan metode konvensional yang dimana peran guru itu adalah mengendalikan atas kebanyakan pembelajaran atau disebut sebagai metode ceramah. Dalam menyampaikan materi secara konvensional guru menggunakan buku sebagai bahan acuan, namun buku yang digunakan dalam menyampaikan materi hanya berisi teks dan gambar yang berwarna hitam putih, yang membuatnya menjadi kurang menarik dan kurang jelas dilihat. Tujuan dari penelitian ini yaitu untuk memudahkan siswa kelas 6 sekolah dasar dalam mempelajari materi tentang Perkembangbiakkan Makhluk Hidup. Kesimpulannya yaitu Aplikasi pembelajaran interaktif perkembangbiakkan makhluk hidup telah selesai dibuat dan aplikasi telah diberi validasi oleh guru IPA SD Gereja Masehi Injili di Minahasa (GMIM) 4 Tondano bahwa aplikasi tersebut dinyatakan layak digunakan dilapangan, berdasarkan hasil pengujian kepada 15 siswa kelas 6, terlihat adanya peningkatan setelah siswa menggunakan aplikasi repromap sebanyak 50% dari nilai pre-test 20% meningkat menjadi 70% dan berdasarkan hasil pengujian kepada 15 siswa kelas 6, menyatakan bahwa sebanyak 60% sangat tertarik menggunakan aplikasi dan 40% lainnya tertarik. Kata kunci — Interaktif, Makhluk Hidup, Multimedia Life Cycle, Pembelajaran, Perkembangbiakkan.